Broken vows - Carter, Les. (Nashville : T. Nelson Publishers, 1991)
How to put the pieces of a marriage back together.
"A Janet Thoma book."
Previously published as: The prodigal spouse. c1990.
Includes bibliographical references (p. 253).
Keywords: Adultery; Marriage -- Religious aspects -- Christianity